2012
DOI: 10.1186/1475-2840-11-111
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid attenuates cardiac fibrosis in Otsuka Long-Evans Tokushima Fatty rats

Abstract: BackgroundHyperglycemia leads to cardiac oxidative stress and an imbalance in glucose homeostasis. Diabetic cardiomyopathy is characterised by cardiac hypertrophy and fibrosis. However, the underlying mechanisms of diabetic cardiomyopathy are not fully understood. This study aimed to investigate the effects of alpha-lipoic acid (ALA) on cardiac energy metabolism, antioxidant effect, and fibrosis in the hearts of Otsuka Long-Evans Tokushima fatty (OLETF) rats.MethodsAnimals were separated into non-diabetic Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Although the ameliorative effects of LA, Resveratol and Quercetin on cardiac oxidative stress has been demonstrated in past studies [35][36][37], the mechanisms have only been partially explained. In this study, the reduced antioxidant capacity in obese mice…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the ameliorative effects of LA, Resveratol and Quercetin on cardiac oxidative stress has been demonstrated in past studies [35][36][37], the mechanisms have only been partially explained. In this study, the reduced antioxidant capacity in obese mice…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Persistent inhibition of GSK3β induces compensatory hypertrophy, inhibits apoptosis and fibrosis, and increases cardiac contractility by suppressing mPTP opening [34]. Given the pivotal role of natural antioxidants in redox regulation, and considerable evidence supporting their ameliorative effects on oxidative stress [35][36][37], current interest is on mechanisms for their cardio-protection. Therefore, the objective of this study was to examine the possible mechanisms for protective effects of Lipoic acid (LA), Quercetin and Resveratrol on oxidative stress induced injury on the heart of obese C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…14) Cardiac fibrosis may cause myocyte hypertrophy and deranged myofibrils, which resulting from oxidative stress, AGEs, cellular growth and proliferation, inflammation, and some involved mediators. 15,16) However, effective treatments of diabetic cardiomyopathy are not available. Thus, identifying the biomarkers involved in cardiac fibrosis may provide novel therapeutic targets for reducing the detrimental effects of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Collective evidence confirmed that ALA is involved in mitochondrial dehydrogenase reactions and has recently gained a considerable amount of attention as a novel antioxidant (Li et al, 2012). ALA has also been regarded as a therapeutic agent for a number of conditions related to cardiovascular disease, including atherosclerosis (Xu et al, 2012), diabetic cardiomyopathy (Hegazy et al, 2013), cardiac fibrosis (Lee et al, 2012). Dietary supplementation with ALA has been successfully employed in a variety of in vivo models: ischemia-reperfusion, heart failure, and hypertension (Ghibu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%